Correlation of sociodemographic factors and intestinal parasites in pregnant women - Roopal, Nipurte; Supriya, Paranjpe; Avani, Koticha; Gita, Nataraj; Preeti, Mehta (International Journal of Research in Medical Sciences, 2019)
Background: Pregnant women often experience more severe intestinal parasitic infections than their non-pregnant counterparts. Intestinal parasitic infections also disturb pregnancy at the maternal and fetal level. Objective of the study was to find out the prevalence of intestinal parasites in pregnant women and its relationship with various socio-demographic factors. Methods: A single stool specimen was collected. A saline and iodine mount was examined microscopically to demonstrate the intestinal parasites. Formol ether Concentration technique was performed to increase the yield of the eggs and larvae. Modified acid-fast staining was done for opportunistic parasitic infections. Results: In this study 300 pregnant women were screened for presence of intestinal parasites. The prevalence of intestinal parasites was 42.67%. Women who practiced hand washing regularly and had knowledge about parasites had lesser infection. The dietary practice of taking green leafy vegetables had protective effect during pregnancy. The prevalence of intestinal parasites was almost same in both rural and urban women. Higher prevalence of intestinal parasites was found in lower socioeconomic class. Women who used river as source of water supply had slightly more prevalence than those who used municipal water. The prevalence of hookworm infection was more in women who never wore sandals. Conclusions: The high prevalence of intestinal parasites in the pregnant women indicates faecal pollution of soil and domestic water supply. Education and awareness regarding intestinal parasites need to be done during their routine antenatal visits. Emphasis should be made on consistent hand washing, consumption of washed leafy vegetables and use of footwear. Deworming of pregnant women should be considered in the national guidelines.